Implementasi Teknik Enkripsi Q-Chiper Pada Keamanan Data Transkrip Nilai Siswa - Khairun Nathassa; Imam Saputra; Rivalri Kristianto Hondro (STMIK Budi Darma, 2022)
Value transcripts often occur when very important data is still done manually because it still has weaknesses, so the value transcripts are easily copied and printed by irresponsible parties, resulting in the application of incorrect values or transcripts or value transcripts whose contents have been engineered. If users do not use a good security system, they will be exposed to security attacks by using the wrong encryption.One of the solutions to the above problems is to encode the transcript data so that its confidentiality can be protected. One of the algorithms that can be applied is the Q-cipher algorithm. By applying the Q-chiper algorithm, the transcript data can be protected from irresponsible parties and can run well and the transcript data can only be accessed by users who have access rights to process the value transcript data.